Migration Waves in Ukraine : Impact on Demographic Shifts and Economic Dynamics - Diakiv, Vladyslav; Shymanska, Kateryna; Brellíková, Miriam; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This bachelor thesis analyzes the demographic and economic consequences of migration waves in Ukraine, focusing on the periods following the 2014 political crisis and the 2022 full-scale Russian invasion. The study investigates the main drivers of emigration, including wage disparities, labor market opportunities, and conflict-induced displacement. It examines the implications of migration, such as the aging population, gender imbalances, demographic and economic shifts, and evaluates the role of remittances and "brain drain" on Ukraine’s economy. The thesis also reviews national and EU migration policies, offering recommendations for more effective migration governance and demographic resilience in Ukraine.
Vedoucí práce: Kateryna Shymanska
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses